Features of the impact of military actions on food security - Pushak, Ya.; Zaichenko, V.; Kornicheva, H.; Petrukha, S.; Kharabovskyi, Yu.; Зайченко, В. В. (My University, 2022)
The sowing campaign is taking place with great difficulty as a result of active military actions in the eastern and southern parts of the country, specializing in the cultivation of grain crops. Seaports are blocked, which creates new threats to global food security. The generalization of analytical data is aimed at characterizing the food security of Ukraine before and during military actions, followed by the designation of possible consequences, including on global food security. The generalizations made prove the need to consolidate the efforts of Ukraine, as one of the world's largest food producers, and international organizations in order to avoid the greatest catastrophe of mankind in its modern history, which will be caused by famine.
Keywords: food security; military actions; famine; food availability; refugees; food